The War in the Pacific - Horan Don; Horan Don; Zimmermna, Morth (A & E Television Networks, 1983)
From the horrifyng attack on Pearl Harbor and the bloddy island-hopping campaign through the Pacific to the atomic bombing of Japan and the surrender on the deck of the U.S.S. Missouri, this nearly two-and-a-half hour presentation is the most comprehensive video produced on the war in the pacific.